The Durbin-Watson Test for Autocorrelation in Nonlinear Models - White, Kenneth J. (The Review of Economics and Statistics, 1992)
This paper shows a simple method of approximating the exact distribution of the Durbin-Watson Test Statistic for first-order autocorrelation in a nonlinear model.The proposed Approximate Nonlinear Durbin-Watson (A.N.D.) test has good size and power when compared to alternatives.